Censorship history lessons. Interferences of the Main Office for the Control of Presentations and Public Performances in the historical and political journalism of the “Nowiny Literackie” weekly (in 1947) - Woźniak-Łabieniec, Marzena (Interdyscyplinarium nauk o mediach i kulturze, 2020)
The goal of the article is to present the censor’s interference in Jaroslaw Iwaszkiewicz’s cultural and literary weekly periodical “Nowiny Literackie”, edited in 1947–1948. The subject of the analysis are only those censorship cuts (from 1947), which concerned articles about political-historical and social issues, showing the events in the country and the government policy (amnesty, celebration of the 3rd May constitution, attitude to the USSR, position of The Polish Socialist Party). The archival materials of the Central Office for Press Control, Publications and Performances, mainly the Report on preventive censorship, became the source material.